Macrodasines A—G, macroline indole alkaloids incorporating fused spirocyclic tetrahydrofuran—tetrahydrofuran and tetrahydrofuran—tetrahydropyran rings - Kam, T.S.; Tan, S.J.; Robinson, W.T.; Komiyama, K. (Elsevier, 2011)
The bark extract of the Malayan Alstonia angustifoliaWall provided the spirocyclic alkaloids macrodasines A—G. The structures of the new compounds were established by analysis of the spectroscopic data and in the case of macrodasines A and B confirmed by X-ray diffraction analysis. Macrodasines A, B, C, and G incorporate fused spirocyclic tetrahydrofuran—tetrahydrofuran rings, while macrodasines D, E, and F incorporate fused tetrahydrofuran—tetrahydropyran rings. Macrodasines B, C, and E were found to show moderate levels of activity in reversing multidrug-resistance in drug-resistant KB cells.